BcCFEM1, a CFEM Domain-Containing Protein with Putative GPI-Anchored Site, Is Involved in Pathogenicity, Conidial Production, and Stress Tolerance in Botrytis cinerea - Zhu, Wenjun; Wei, Wei; Wu, Yayun; Zhou, Yang; Peng, Fang; Zhang, Shaopeng; Chen, Ping; Xu, Xiaowen (Frontiers in Microbiology, 2017)
We experimentally isolated and characterized a CFEM protein with putative GPI-anchored site BcCFEM1 in Botrytis cinerea. BcCFEM1 contains a CFEM (common in several fungal extracellular membrane proteins) domain with the characteristic eight cysteine residues at N terminus, and a predicted GPI modification site at C terminus. BcCFEM1 was significantly up-regulated during early stage of infection on bean leaves and induced chlorosis in Nicotiana benthamiana leaves using Agrobacterium infiltration method. Targeted deletion of BcCFEM1 in B. cinerea affected virulence, conidial production and stress tolerance, but not growth rate, conidial germination, colony morphology and sclerotial formation. However, over expression of BcCFEM1 did not make any observable phenotype change. Therefore, our data suggested that BcCFEM1 contributes to virulence, conidial production and stress tolerance. These findings further enhance our understanding on the sophisticated pathogenicity of B. cinerea beyond necrotrophic stage, highlighting the importance of CFEM protein to B. cinerea and other broad-host-range necrotrophic pathogens.